2021
DOI: 10.9734/ajrb/2021/v8i430187
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant Activity of Leaf of Hoslundia opposita Vahl and Docking of its Phytochemical Components with Uropathogenic Strain F11(ID:3NRP) and NFeoB from Escherichia coli BL21(ID:5FH9)

Abstract: Hoslundia opposita Vahl is a multi-purpose medicinal plant used traditionally to treat gonorrhea, cystitis, cough, fever, snake bites, convulsion in many parts of Africa. The objectives of this research are to evaluate the phytochemical profile, antioxidant activity of the leaves of Hoslundia opposita Vahl and to dock its phytochemical components with uropathogenic Escherichia coli strain F11(ID:3NRP) and NFeoB from Escherichia coli BL21(ID:5FH9). Harborne’s method was used for the identification of the class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
2
2
0
Order By: Relevance
“…This is in agreement with previous studies in that different parts of the plant extracted with more polar solvents showed high TPC and TFC [24]. The TPC and TFC reported in the present study were found to be high when compared to the reports elsewhere [11,35]. The antioxidant properties are correlated with the phenolic content of any plants which act as hydrogen donors, reducing agents, and are capable of scavenging free radicals [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies in that different parts of the plant extracted with more polar solvents showed high TPC and TFC [24]. The TPC and TFC reported in the present study were found to be high when compared to the reports elsewhere [11,35]. The antioxidant properties are correlated with the phenolic content of any plants which act as hydrogen donors, reducing agents, and are capable of scavenging free radicals [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…In Uganda, the identified compounds in essential oils of this plant that have also been found in our study were; germacrene D, phytol and palmitic acid [64]. Edewor et., al [65] identified compounds from the methanolic extract of H.opposita Vahl from Nigeria and found 17 compounds of which Hexadecanoic acid, methyl ester, n-hexadecanoic acid, Octadecanoic acid were also identified in this study. However, the same authors did not find alkaloids and tannins in the quantitative phytochemistry which is opposed to this study.…”
Section: Retention Timesupporting
confidence: 57%
“…Traditionally, the plant parts have beenu sed for the treatment of menstrual cycle disorder (Nigatu, 2004), constipation, diarrhea, dysentery (Kisangau et al, 2007), arthritis, rheumatism, venereal diseases, malaria (Kasali et al, 2014), sleep disorder, anaemia (Nguyen et al, 2016), diabetes mellitus, microbial and fungi infections (Ezenyi et al, 2016). Additionally, scientific investigations have demonstrated that the methanol and aqueous extracts of the plant leaves possess antioxidant effect (Pieme et al, 2014;Edewor et al, 2021). However, the antioxidant activity of the ethylacetate and chloroform extracts of the plant leaves together with the antiglycation potential of these extracts remain a knowledge lacuna that needs to be bridged.…”
Section: Introductionmentioning
confidence: 99%